Technologies Of Using "Communicative Training" In Teaching English To 9-11th Grade Students In Secondary Schools - D.Sh., Akramova (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The article provides information on the effectiveness of the use of "communicative learning" technology in teaching English in grades 9-11 in secondary schools, the effectiveness of language development in students and its application to the educational process. Also; methods of developing English language skills in students through communicative training technology, methods of using innovative teaching methods.